Aminothiazole-derived N, S, Fe-doped graphene nanosheets as high performance electrocatalysts for oxygen reduction. Issue 96 (9th October 2015) - Chen, Chi; Yang, Xiao-Dong; Zhou, Zhi-You; Lai, Yu-Jiao; Rauf, Muhammad; Wang, Ying; Pan, Jing; Zhuang, Lin; Wang, Qiang; Wang, Yu-Cheng; Tian, Na; Zhang, Xin-Sheng; et al.
Abstract : N, S, Fe-doped graphene nanosheets with high ORR electrocatalytic activity were directly synthesized from aminothiazole through Fe catalysis under heat-treatment. Abstract : N, S, Fe-doped graphene nanosheets were directly synthesized from aminothiazole, a precursor molecule that contains N and S atoms, through Fe catalysis under heat treatment. The graphene nanosheets exhibited high electrocatalytic activity toward oxygen reduction reaction in both acidic and alkaline media during rotating disk electrode half-cell and fuel cell tests.